I'm working through the book Introductory Econometrics and stumbled across a statement regarding the variance of the error term, $u$, of a linear regression model, $y = \beta_0 + \beta_1 x + u$.

To give some context, two assumptions were introduced beforehand:

  1. Zero conditional mean, i.e. $E(u|x) = 0$, and
  2. Homoskedasticity, i.e. $Var(u|x) = \sigma^2$.

Then, the argument goes on as follows:

Because $Var(u|x) = E(u^2|x) - [E(u|x)]^2$ and $E(u|x) = 0$, $\sigma^2 = E(u^2|x)$, which means $\sigma^2$ is also the unconditional expectation of $u^2$.

While I understand the first part of the sentence, I have no idea where the bolded part comes from. It seems to say that because $E(u^2|x)=\sigma^2$ (i.e. the conditional expectation of $u^2$), it follows that $E(u^2) = \sigma^2$ (i.e. the unconditional expectation of $u^2$). I might be missing something very basic here, but I can't figure it out.


1 Answer 1


It follows from the law of iterated expectations: the expected value of the conditional expected value of $u$ given $X$ is the same as the expected value of $u$.

$$E[u^2] = E[E[u^2|X]] = E[\sigma^2] = \sigma^2$$

  • 2
    $\begingroup$ Wooldridge, Introductory Econometrics, Appendix B, Property CE.4, page 687. $\endgroup$
    – Sergio
    Oct 13, 2020 at 10:56

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.